Association of hOGG1‐Cys variants with occurrence of p53 and EGFR deletion mutations in non‐small cell lung cancer. Issue 4 (28th December 2020) - Chen, Ming‐Jenn; Shen, Ching‐Ju; Wang, Lee; Chen, Po‐Ming; Chen, Chih‐Yi; Lee, Huei
Abstract: Background: The human 8‐oxoguanine DNA glycosylase 1 ( hOGG1 ) gene encodes a DNA glycosylase that removes 8‐hydroxy‐2‐deoxyguanine (8‐OH‐dG) DNA damage to protect against gene mutations. The association of hOGG1 Ser326Cys polymorphism with lung cancer risk has predicted that hOGG1 ‐Cys variants are less effective at removing 8‐OH‐dG damage from DNA; therefore, these variants might show an increased occurrence of tumor suppressor gene and oncogene mutations. However, no evidence has yet supported this hypothesis. Methods: Direct sequencing was performed to examine the mutations of p53 and EGFR genes in lung tumors from patients with non‐small cell lung cancer (NSCLC). Polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) was used to examine hOGG1 Ser326Cys polymorphism in this study population. Results: A total of 99 p53 ‐mutated and 99 EGFR ‐mutated patients with NSCLC were selected to explore the possible associations of these mutations with hOGG1 Ser326Cys polymorphism. The p53 ‐mutated and EGFR ‐mutated patients were divided into nondeletion and deletion subgroups. P53 deletion mutations were more commonly observed in male than in female patients ( P = 0.030). However, EGFR exon 19 deletion mutations were more prevalent in female and adenocarcinoma patients than in male and squamous cell carcinoma patients ( P = 0.028 for genders, P = 0.017 for tumor histology). Interestingly, p53 and EGFR exon 19 deletion mutations were more frequent in patients with hOGG1 Ser/Cys + Cys/Cys hOGG1 ‐Cys variants than with the hOGG1 Ser/Ser genotype ( P = 0.010 for p53, P = 0.032 for EGFR ). Conclusions: We suggest that the association of hOGG1 Ser326Cys polymorphism with lung cancer risk could be partially explained by increases in p53 and EGFR deletion mutations. Key points: Significant findings of the study: NSCLC patients with hOGG1 ‐Cys variants may have a higher risk of p53 and EGFR deletion mutations than with hOGG1 Ser/Ser genotype. What this study adds: NSCLC patients with hOGG1 ‐Cys variants might be helpful to predict patients having higher risk of EGFR exon 19 deletion mutations and these patients who were treated with gefitinib or erlotinib could be a higher risk to occur EGFR T790M mutation. Abstract : NSCLC patients with hOGG1‐Cys variants may have higher risk of p53 and EGFR deletion mutations than with hOGG1 Ser/Ser genotype. NSCLC patients with hOGG1‐Cys variants might be helpful to predict patients with higher risk of EGFR exon 19 deletion mutations and these patients who were treated with gefitinib and erlotinib were more common to occur EGFR T790M mutation.